2016
DOI: 10.18632/oncotarget.12295
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral radiofrequency hyperthermia-enhanced direct chemotherapy of pancreatic cancer

Abstract: PurposeTo investigate the technical feasibility of using ultrasound-guided intratumoral radiofrequency hyperthermia (RFH) to enhance local chemotherapy of rat orthotopic pancreatic cancers.Materials and MethodsOrthotopic pancreatic cancer masses were established by inoculating luciferase/mCherry labeled-pancreatic cancer cells into the pancreatic tails of Lewis model rats via a laparotomy approach. Twenty-four rats with pancreatic cancer and 24 mice with subcutaneous pancreatic cancer xenografts in four study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…For pancreatic cancer, the efficacy of HT has been validated in the preclinical setting. For example, in subcutaneous pancreatic cancer xenografts in rats and mice, the combination of gemcitabine and HT was more effective than gemcitabine or HT alone [35][36][37]. For pancreatic cancer patients, however, data are limited.…”
Section: Introductionmentioning
confidence: 99%
“…For pancreatic cancer, the efficacy of HT has been validated in the preclinical setting. For example, in subcutaneous pancreatic cancer xenografts in rats and mice, the combination of gemcitabine and HT was more effective than gemcitabine or HT alone [35][36][37]. For pancreatic cancer patients, however, data are limited.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, RFH can increase cell apoptosis level in murine pancreatic cancer cell lines and pancreatic cancer tumors, as manifested by flow cytometry assay, which demonstrated the highest percentage of apoptotic cells with combination therapy in in-vitro experiments. 23 Furthermore, in this study, we investigated the potential mechanisms of intratumoral RFH-enhanced chemotherapeutic effects in cancers. Our findings showed that: (a) some factors related to immune responses, such as HSP70, IL-1β, and TNF-ɑ in tumor tissues, were elevated significantly after combination therapy, indicating HSP70-dependent local immune responses may involve in the mechanisms of the therapy; (b) both in vitro and in vivo experiments showed significant changes in Bax, Bcl-2, and caspase-3 expressions in the pancreatic cancer cell groups with combination therapy, compared to other controls, suggesting caspase-3-depended cell apoptosis pathways may also involve in the enhancement of RFH-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Rat models with orthotopic pancreatic cancer were created in Lewis rats weighted 150–200 ​g and RF hyperthermia was performed as described in our previous study. 23 When the orthotopic pancreatic tumors had grown to 5–10 ​mm in diameter, six rats in each of four groups were treated by (a) intratumoral injections of gemcitabine (100-mg/kg for rats), followed by RFH at approximately 42 ​°C for 30 minutes; (b) intratumoral injection of gemcitabine alone; (c) 30-min RFH alone; and (d) injection of 100 ​μL PBS to serve as a control. All groups of rats were sacrificed 24 ​h after the treatments for tumor collection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As device development and clinical investigations progress, it may be possible to deliver hyperthermia with these deployable applicators as an adjunct to a chemotherapy regimen such as conventional FOLFIRNOX [20,84] or immunotherapy [1,2,85,86]. As supported by many key studies, the localized heat can impact the blood flow and permeability of desmoplastic tumors [5][6][7]10,87], thereby increasing drug uptake [88] and activity [11,89], or directly targeting release of thermally sensitive liposomes [16][17][18][20][21][22]80,81] or nanoparticles [13,14].…”
Section: Discussionmentioning
confidence: 99%